An Overview on Engineering Bio-Treatment Methods for Effluent in Food Processing Industries (Global Journal of Science Frontier Research, 2023)
The highly toxic materials appearing in the food processing effluents are persistent on the natural ecosystem. The resultant effect is magnifying throughout the food chain and adversely affecting both public health and environmental health. So, effluent from food processing industries havereceived extensive research awareness. This review examines the adapted engineering bio-treatment methods for effluent and their treatment mitigations. Effluents from various food processing industries are also discussed. Volatile organic compounds (VOC) are emitted from this effluent and differ in chemical formation, amount, and possible threat. Natural methods used for their reduction have definite advantages and disadvantages. Risk reduction evaluations are the basic step for the treatment methods. Different physical, chemical, and biological treatment technologies have been applied to remove microorganisms from effluent,each having inherent merits and limitations. The simultaneous novelty of bio-energy and bio-treatment of effluent made this work outstanding.
Keywords: bio-treatment; effluent; food processing; industry; microorganism